2020
DOI: 10.1063/5.0005398
|View full text |Cite
|
Sign up to set email alerts
|

The peculiar size and temperature dependence of water diffusion in carbon nanotubes studied with 2D NMR diffusion–relaxation D –T2eff spectroscopy

Abstract: It is well known that water inside hydrophobic nano-channels diffuses faster than bulk water. Recent theoretical studies have shown that this enhancement depends on the size of the hydrophobic nanochannels. However, experimental evidence of this dependence is lacking. Here, by combining two-dimensional nuclear magnetic resonance diffusion–relaxation (D–T2eff) spectroscopy in the stray field of a superconducting magnet and molecular dynamics simulations, we analyze the size dependence of water dynamics inside C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(54 citation statements)
references
References 75 publications
11
43
0
Order By: Relevance
“…For large CNTs, a bulk-like density profile is observed near the nano-tube center in agreement with previous studies [ 8 , 34 ]. For the 3.0 nm-CNT, we observed two additional water layers consistent with the NMR experiments [ 26 ]. Density maps corresponding to the oxygen occurrence during MD simulation in xy direction are shown in Figure S1 (Supporting Information (SI)) .…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…For large CNTs, a bulk-like density profile is observed near the nano-tube center in agreement with previous studies [ 8 , 34 ]. For the 3.0 nm-CNT, we observed two additional water layers consistent with the NMR experiments [ 26 ]. Density maps corresponding to the oxygen occurrence during MD simulation in xy direction are shown in Figure S1 (Supporting Information (SI)) .…”
Section: Resultssupporting
confidence: 85%
“…On the other hand, inside 3.0 nm, 3.5 nm, and 10 nm, it was observed that water diffuses faster in the central sheets, compared to others. These results were experimentally verified by our group using NMR spectroscopy [ 26 ]. Structural and vibrational studies [ 39 , 40 ] have also shown that water confined inside a CNT of size 3.0 nm acquires ice-like clusters, showing cooperative motion with high diffusion.…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations